A multi-level perspective on trust, collaboration and knowledge sharing cultures in a highly formalized organization. Issue 9 (24th March 2021) - Alshwayat, Dana; MacVaugh, Jason Alexander; Akbar, Hammad
Abstract : Purpose: The purpose of this study is to investigate organizational culture's perceived importance and practice as it unfolds across hierarchal layers of a formalized organization. Organizational culture is important in innovation and change and becomes significant if its importance and practice are shared across all levels of an organization. Highly formalized organizations are not an exception to this. Yet, there is a shortage of empirical evidence on how the organizational culture's perceived importance and practice unfold across the senior-management, middle-management and operational levels of a formalized organization. Design/methodology/approach: Applying a theoretical frame incorporating information asymmetry, knowledge sharing and cultural participation, this paper examined three important facets of culture, namely, trust, collaboration and knowledge-sharing. Using a Jordanian bank's case study, this paper collected data using a mixed-methods approach; quantitative to identify variations across levels and, subsequently, qualitative to explore the nuanced patterns in the perceived importance and practice of the three facets across different organizational levels in the context of a formalized organization. Findings: The findings suggest that the importance and practice of the three cultural facets are shared, as well as differentiated across organizational levels based on purposiveness, person/situation-dependency and nature of work and nature/relevance of knowledge. Originality/value: Using a multi-level lens provided insight not yet gained by current work in the field. This allowed us to unearth nuanced differences in the perception of organizational culture across organizational hierarchies. The paper contributes to the scholarship on organizational culture in the context of formalized organizations and to managerial practice by offering insights on how a shared practice of trust, collaboration and knowledge sharing is distributed across organizational levels, not captured before. This paper also suggests propositions related to each of three cultural facets, not spelled out before.